NHP BurkPx: A multiplex serodiagnostic bead assay to monitor Burkholderia pseudomallei exposures in non-human primates - Kimberly R. Celona; Austin B. Shannon; Derek Sonderegger; Jinhee Yi; Fernando P. Monroy; Christopher Allender; Heidie Hornstra; Mary B. Barnes; Elizabeth S. Didier; Rudolf P. Bohm; Kathrine Phillippi-Falkenstein; Daniel Sanford; et al. (Public Library of Science (PLoS), 2023)
Background Melioidosis is a disease caused by the bacterium Burkholderia pseudomallei, infecting humans and non-human primates (NHP) through contaminated soil or water. World-wide there are an estimated 165,000 human melioidosis cases each year, but recordings of NHP cases are sporadic. Clinical detection of melioidosis in humans is primarily by culturing B. pseudomallei, and there are no standardized detection protocols for NHP. NHP are an important animal model for melioidosis research including clinical trials and development of biodefense countermeasures. Methodology/Principle findings We evaluated the diagnostic potential of the multiple antigen serological assay, BurkPx, in NHP using two sera sets: (i) 115 B. pseudomallei-challenged serum samples from 80 NHP collected each week post-exposure (n = 52) and at euthanasia (n = 47), and (ii) 126 B. pseudomallei-naïve/negative serum samples. We observed early IgM antibody responses to carbohydrate antigens followed by IgG antibody recognition to multiple B. pseudomallei protein antigens during the second week of infection. B. pseudomallei negative serum samples had low to intermediate antibody cross reactivity to the antigens in this assay. Infection time was predicted as the determining factor in the variation of antibody responses, with 77.67% of variation explained by the first component of the principal component analysis. A multiple antigen model generated a binary prediction metric ( Conclusion/Significance We employed a previously standardized assay for humans, the BurkPx assay, and assessed its diagnostic potential for detection of B. pseudomallei exposure in NHP. The assay is expected to be useful for surveillance in NHP colonies, in investigations of suspected accidental releases or exposures, and for identifying vaccine correlates of protection. Author summary Melioidosis is a disease caused by the soil-dwelling bacterium Burkholderia pseudomallei, a Tier 1 Select Agent by the US Centers for Disease Control and Prevention (CDC), with the ability to naturally infect humans and non-human primates (NHP). Although melioidosis diagnosis in humans has been formally outlined, there is no standardized test available for B. pseudomallei exposure and melioidosis in NHP. NHP are important animal models in melioidosis research in addition to other scientific research. The goal of this study was to formally evaluate the first extensive serodiagnostic test for detection of B. pseudomallei exposure in NHP. The BurkPx assay comprised 21 B. pseudomallei specific antigens and was previously standardized in humans. Early IgM antibody responses were noted to carbohydrates whilst IgG antibody responses were mounted to multiple proteins during the second week of infection. The assay elicited low background reactivity to B. pseudomallei-naive NHP. Data collected from the BurkPx assay was fed into a multiple antigen model, which produced a